Studying psychology: Louw, J (1992) What about studying psychology? Pretoria: Academia. - du Preez, Jan (PINS-Psychology in Society, 2026)
"Psychologists study so many things, and carry out such a wide variety of activities, that it bewilders even the advanced student of the discipline."(p1) Louw argues that in spite of this confusing picture, psychology is the most popular subject at university, based on registration figures. Part 1 of this book sets out to put this popularity in perspective, suggesting that prospective students believe that the study of psychology will equip them with a whole range of communication skills, the ability to conduct research and related to this, the ability to use statistics and computers. The expectation of psychology student that their interpersonal skills will be developed, is usually only met in post graduate training. Other more general skills, related to a university education, include problem solving, critical thinking, organising information, adaptability, creativity and leadership.